Study of Islam and media in contemporary Nigeria - Ashimi, Tijani Ahmad (s.n, 2012)
Islam is one of the major religions in contemporary Nigeria, this research studies and explores Islam and secular media (Nigerian Print Media) in contemporary pluralistic Nigeria. By applying descriptive and analytically approaches, the research aims to explore the development of Islam in post-independent Nigeria with particular reference to the north and south West Nigeria respectively. The research also explores the portrayal of Islam by Nigerian secular media, yet, for the purpose of research some famous print media are selected for analysis